Effect of Primary α Phase on the Plastic Deformation Mechanism of Ti–10Mo–1Fe Alloys at Room Temperature. Issue 5 (4th December 2021) - Wang, Qingjuan; Gao, Beite; Wang, Wei; Xin, Shewei; Sun, Yaling; Wang, Kuaishe
Abstract : Through room‐temperature compression tests, the microstructure evolution and room‐temperature plastic deformation mechanism of a β‐type Ti–10Mo–1Fe alloy, which exhibits a primary α phase after solution treatment at 780 °C, are studied. When the deformation is small, the existence of the primary α phase makes the distribution of twins between grains uneven. A small amount of intragranular twins grows to the intragranular α phase, and then stops growing. The grain boundary α phase (GBα) plays an important role in inhibiting the growth of twin laths to a certain extent. When the deformation is large, compression cracks appear at the α/β phase interface. The α/β phase interface is weak, and the deformation along the 45° direction is relatively large. Owing to the existence of the primary α phase, the ultimate tensile strength of the alloy increases to 934.5 MPa, and the elongation reaches 21.7%. The room‐temperature plastic deformation mechanism of the Ti‐10Mo‐1Fe alloy solution treated at 780 °C is dominated by 332 <113> twins, as well as by a small amount of 112 <111> twins (0.57%) and stress‐induced orthorhombic martensite α" phase (2.5%). Abstract : The room‐temperature plastic deformation mechanism of Ti‐10Mo‐1Fe alloy solid solution at 780°C is dominated by 332<113> twins, accompanied by a small amount of 112<111> twins (0.57%) and stress‐induced orthorhombic martensite α" phase (2.5%). The primary α phase and deformation products hinder or inhibit the growth of twins, thereby affecting its mechanical properties.